2017
DOI: 10.1007/s40429-017-0145-z
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Effects of Cannabis Use Disorder: Evidence to Support a Cultural Neuroscience Approach

Abstract: Purpose of review Cannabis use disorders (CUDs) are prevalent worldwide. Current epidemiological studies underscore differences in behaviors that contribute to cannabis use across cultures that can be leveraged towards prevention and treatment of CUDs. This review proposes a framework for understanding the effects of cross-cultural differences on psychological, neural, and genomic processes underlying CUDs that has the potential to inform global policies and impact global public health. Recent findings We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…Cultural differences: Cultural factors significantly shape the manifestation of Cannabis Use Disorders (CUDs), with diverse legal and social climates influencing individuals' behaviors toward seeking treatment [ 64 ]. For instance, Australia's harm-reduction policy and public healthcare system may have a distinct impact on treatment outcomes compared to the United States [ 64 ]. These differences underscore the importance of considering cultural contexts in addressing CUDs and tailoring interventions to meet the unique needs of various communities.…”
Section: Reviewmentioning
confidence: 99%
“…Cultural differences: Cultural factors significantly shape the manifestation of Cannabis Use Disorders (CUDs), with diverse legal and social climates influencing individuals' behaviors toward seeking treatment [ 64 ]. For instance, Australia's harm-reduction policy and public healthcare system may have a distinct impact on treatment outcomes compared to the United States [ 64 ]. These differences underscore the importance of considering cultural contexts in addressing CUDs and tailoring interventions to meet the unique needs of various communities.…”
Section: Reviewmentioning
confidence: 99%
“…A study by Sznitman and Bretteville-Jensen (2015) found that perceived medicinal benefits of cannabis predicted an individual's support for cannabis legalization. A recent review found that willingness to acknowledge CUD-related symptoms vary depending on the region [51]. However, participating in cannabis dealing, supporting cannabis legalization, and willingness to acknowledge CUD symptoms do not directly equate to increased/decreased risk for CUD.…”
Section: Macrosystem Factors For Cudmentioning
confidence: 99%
“…Culture, however, must be operationalized. Cultural influences in CUD development can be defined as the normative culture of the region that is a collection of behaviors considered appropriate, but culture can also be described as a dynamic interaction of environmental, biological, and psychological factors that contribute to behavior [50,51]. Cultural influences are an essential component in the development of addiction and must be recognized in research.…”
Section: A Bioecological Framework For Cud Towards Understanding Cannabis Policy Impactsmentioning
confidence: 99%
“…Cannabis culture (i.e. an environment that facilitates a systematic set of cannabis‐related behaviours during an extended period of time) may impact upon cannabis‐related health effects . Cross‐cultural studies are largely missing; however, social factors and willingness to acknowledge cannabis use disorder (CUD) symptoms have been found to differ between legal cultures .…”
Section: Report Overviewmentioning
confidence: 99%